IMPLEMENTING DIDACTIC PRINCIPLES IN WORKING WITH VOCABULARY (Scientific journal of the Fergana State University, 2025)
This article analyzes the introduction of didactic principles in working with vocabulary, the relevance of previously learned foreign language knowledge to the topic of vocabulary teaching, and the possibility of teaching based on the similarities between languages.